The Role of Management Accounting Information in Short-Term and Long-Term Managerial Decision-Making at Xavier Marks Tjandra East - Steven Nathanael Handoko; Slamet Riyadi (Indonesian Journal Publisher, 2025)
This study analyzes the role of management accounting information in supporting short-term and long-term managerial decisions at Xavier Marks Tjandra East. Using a descriptive qualitative approach, data were obtained through observation, documentation, and interviews with the Principal, Legality division, and Finance division. The findings show that management accounting, especially cost and differential accounting, is essential for various decisions. Short-term uses include determining commissions, evaluating property legality, and selecting property types. Long-term uses involve fixed asset investment, branch and human resource expansion, and planning independent property development. The study concludes that integrating management accounting information strengthens business strategies and supports company sustainability. The researcher recommends enhancing this function with integrated systems, improved SOPs, and continuous management training.